TYPE AND FREQUENCY SPEECH ERRORS IN ENGLISH SPEAKING AMONG ENGLISH DEPARTMENT STUDENTS IN GORONTALO - Muziatun Muziatun; Rasyah Algirifaldi S. Tayeb; Dela Agustina; Sri Minantry Subu; Mutia Mahabu; Nur Adelia Leolita Akib (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study aims to identify the types and frequency of speech errors in English speaking among English Department students in Gorontalo. Speaking is an important skill in language learning; however, many students still experience difficulties that lead to various errors during communication. These errors often appear in the form of hesitation, repetition, and self-correction during speaking activities. This study employs a descriptive qualitative method supported by simple quantitative analysis. Data were collected through audio recordings of students’ speaking tasks lasting 1-2 minutes, involving 10 students as participants. The data were then analyzed by identifying, classifying, and calculating the frequency of speech errors based on specific categories. The results show that there are four types of speech errors, namely filled pauses, repetition, silent pauses, and self-correction. Filled pauses are found to be the most dominant type of error, while self-correction appears the least frequently. These findings indicate that the dominance of filled pauses reflects a high cognitive load during the speech production process, as students manage real-time language planning. This study concludes that speech errors are a natural part of second language learning and can be reduced through continuous speaking practice and improved confidence in using english.